Distinctiveness and serial position functions in implicit memory. Issue 2 (17th February 2018) - Bireta, Tamra J.; Gabel, Andrew J.; Lamkin, Rebecca M.; Neath, Ian; Surprenant, Aimée M.
ABSTRACT: Serial position functions, with their characteristic primacy and recency effects, are ubiquitous in episodic memory tasks, and have also been observed in tasks tapping semantic memory. However, only one experiment, [Raanaas, R. K., & Magnussen, S. (2006a). Serial position effects in implicit memory. European Journal of Cognitive Psychology, 18, 398–414. doi:10.1080/09541440500162065 ], has demonstrated primacy and recency effects in implicit memory using an indirect memory test. In Experiment 1, we replicate this finding and in Experiment 2, we confirm a prediction that holds only if the serial position function observed in Experiment 1 was a "real" serial position function. These results confirm the presence of serial position functions in implicit memory and also support a general prediction of the relative distinctiveness principle that serial position functions should obtain whenever a set of items are ordered along a relevant dimension.